2013
DOI: 10.5194/angeo-31-31-2013
|View full text |Cite
|
Sign up to set email alerts
|

A linear model for amplitude modulation of Langmuir waves in weak electron-beam plasma interaction

Abstract: Abstract.A simple linear approach to the phenomenon of amplitude modulation of Langmuir waves in weak beam plasma interaction is presented. During the short growth phase of the instability and within the longer period after saturation, the waves are described by their linear kinetic dispersion properties.The amplitude modulation appears as result of the beating of waves with different wavelengths and amplitudes that have grown from noise in the initial phase. The Langmuir wave fields are calculated via FFT (fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…e Ey amplitude increases 30 times during 40 < ω pe t < 85. According to Figure 2, the wavelength of quasilinear perturbations along the y-direction at ω pe t∼40 is λ/λ D ∼150 which is in good agreement with that predicted by theory [11] as λ/λ D ∼2π V d,b /V th,e ∼2π × 6 × 10 7 /2.65 × 10 6 � 142.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…e Ey amplitude increases 30 times during 40 < ω pe t < 85. According to Figure 2, the wavelength of quasilinear perturbations along the y-direction at ω pe t∼40 is λ/λ D ∼150 which is in good agreement with that predicted by theory [11] as λ/λ D ∼2π V d,b /V th,e ∼2π × 6 × 10 7 /2.65 × 10 6 � 142.…”
Section: Resultssupporting
confidence: 84%
“…Yi et al [10] presented a comparative study of the dynamics of the electron beam-plasma system in two spatial dimensions by means of particle-in-cell (PIC) simulation and quasilinear theory, and it is found that the quasilinear theory quite adequately accounts for most important features associated with the simulation result. In another theoretical study, Baumgartel [11] described a simple linear approach to the phenomenon of amplitude modulation of Langmuir waves in weak beam-plasma interaction and found out that the resulting waveforms in temporal representation are quite similar to those observed by the spacecraft. Gurnett et al [12] presented observations of the parametric decay and spatial collapse of Langmuir waves driven by an electron beam streaming into the solar wind from the Jovian bow shock.…”
Section: Introductionmentioning
confidence: 82%
“…In a previous paper (Baumgärtel, 2013, hereafter referred to as B1), a simple linear model of the gentle beam-plasma instability has been developed that turned out to be capable of explaining primary characteristics of the irregular type of the modulation. The model, however, fails in describing coherent modulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 2α = 90 • (see figure 6(c)), the amplitude modulation of E x becomes disordered, and the periodicity of B z envelope becomes weaker. When 2α = 30 • (see figure 6 According to the [40] and [41], the amplitude modulation of E x can be a result from beating of plasma waves with different frequencies. In particular, if there exists an obvious double peak in the spectrum, which means two different wave modes close with each other, then the beating will be coherent and the amplitude modulation will be periodic.…”
Section: Discussion On Performance Of the Radiation Sourcementioning
confidence: 99%